THE THE DIFFERENCE OF FLEXIBILITY BETWEEN CONTRACT RELAX STRETCHING DIRECT AND MUSCLE ENERGY TECHNIQUE FOR ANY STUDENT AT SMA NEGERI 1 GIANYAR - Herlangga, Putu Bayu; Andayani, Ni Luh Nopi; Wahyuni, Nila (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 2 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i02.p09, 2018)
ABSTRACT Hamstring muscle is an important postural muscle group in body movement during activities such as standing, walking running and jumping. Hamstring that interferes will disrupt the balance of other muscle performance, a common muscle disorder is muscle shortening. Shortening of this muscle causes a person more susceptible to injury. The purpose of this study was to determine the effectiveness of contract relaxation stretching direct intervention with muscle energy technique in improving the flexibility of Hamstring, Sit and Reach Test is used as a measuring tool. This study used a pretest-postest two group experimental design. The sample of 22 people is divided into two groups. Group 1 received contract relax stretching direct, group 2 muscle energy technique. Test normality with Shapiro wilk test. Paired sample t-test is used in hypothesis testing. Group 1 p = 0,000 average 12,6 ± 2,907 while group 2 p = 0,000 average 11,2 ± 3,452. This data means a significant increase in Hamstring's flexibility in both groups. Different test of both groups with independent sample t-test got result p = 0,313. The data means that there is no significant difference between the two interventions on increased hamstring flexibility. Keyword s : The flexibility of Hamstring muscle, contract relax stretching Direct , muscle energy technique, sit and reach test